2016
DOI: 10.1111/aos.13241
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of vitamin D levels with tear film stability and secretion in patients with dry eye syndrome

Abstract: Tear break-up time (TBUT) and secretion were correlated with serum vitamin D levels. Vitamin D status may be an important factor for dry eye syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 47 publications
6
41
0
2
Order By: Relevance
“…Vitamin D is a potent antioxidant, and patients with increased levels of serum vitamin D levels were found to have increased BUT and tear secretion (Jin et al. ). Serum vitamin D levels are positively correlated to tear vitamin D levels, with tear vitamin D levels being higher than that of serum levels (Sethu et al.…”
Section: Future Studies and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D is a potent antioxidant, and patients with increased levels of serum vitamin D levels were found to have increased BUT and tear secretion (Jin et al. ). Serum vitamin D levels are positively correlated to tear vitamin D levels, with tear vitamin D levels being higher than that of serum levels (Sethu et al.…”
Section: Future Studies and Challengesmentioning
confidence: 99%
“…The importance of vitamin C supplementation for the health of the ocular surface and tear has been shown in diabetic people, who are at risk for dry eye (Peponis et al 2002(Peponis et al , 2004. Vitamin D is a potent antioxidant, and patients with increased levels of serum vitamin D levels were found to have increased BUT and tear secretion (Jin et al 2017). Serum vitamin D levels are positively correlated to tear vitamin D levels, with tear vitamin D levels being higher than that of serum levels (Sethu et al 2016).…”
Section: Future Studies and Challengesmentioning
confidence: 99%
“…Essential fatty acids should be considered for routine use in SM-exposed victims. Jin et al [2016] reported that tear secretion and tear film break-up time are associated with the serum level of vitamin D, and thus the deficiency of this vitamin plays an important role in dry eye patients. Oral administration of pilocarpine and cevimeline is documented in dry eye patients [Ono et al, 2004;Kawakita et al, 2015], results in increase of tear film break-up time, improve healing of corneoconjunctival epithelium, and decrease in ocular symptoms [Ono et al, 2004;Kawakita et al, 2015].…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 99%
“…The direct effect of vitamin D in dry eye management is controversial. Jin et al [2016] reported that tear secretion and tear film break-up time are associated with the serum level of vitamin D, and thus the deficiency of this vitamin plays an important role in dry eye patients. Jee et al [2016] did not support these findings and showed that vitamin D is more effective in the management of macular disease and diabetic retinopathy than dry eye disease.…”
Section: Medical Managementsmentioning
confidence: 99%
“…For example, Jee et al (2016) reported no effect, whereas Yildirim et al (2016) and Kurtul (2015b) suggested good improvements. Jin et al (2016) observed that TBUT was shorter in people with vitamin D deficiency, but did not measure a significant impact on OSDI scores or fluorescein staining (Jin et al, 2016).…”
Section: Impact Of Vitamin D Supplements On Dry Eyementioning
confidence: 96%